2007
DOI: 10.1002/qua.21318
|View full text |Cite
|
Sign up to set email alerts
|

The water mediated ring closing in the formose reaction

Abstract: ABSTRACT:In this work, we investigate the ring closing mechanisms leading to the formation of formose by high-level ab initio theoretical calculations. We suggest that a water-mediated ring closing mechanism (through the use of H 3 O ϩ ) is energetically the most favorable pathway for this process. Solvent effects have also been computed and the results further confirm our assertion of the catalytic effect of water in the ringclosing mechanism of the formose reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The values for formation of S5 ϩ through TS1 were high, but should also be considered as possible mechanisms. Hydronium ion may have dual catalytic properties in these mechanisms [indicated by our recent work on the Nazarov reaction (Jalbout et al, 2007)]; therefore consideration was given for its involvement in the ring-closing mechanism of S1 to yield cyclic product S5 ϩ . This occurs through TS2, which has a forward barrier (⌬H F7 ) of Ϫ7.4 kcal/mol (MP2) and Ϫ6.9 kcal/mol (CCSD (T)//MP2) and an energy of reaction of around Ϫ25 kcal/mol at both the MP2 and CCSD (T)//MP2 levels of theory.…”
Section: H 3 O ϩ Addition Of Dimer To Intermediatementioning
confidence: 99%
“…The values for formation of S5 ϩ through TS1 were high, but should also be considered as possible mechanisms. Hydronium ion may have dual catalytic properties in these mechanisms [indicated by our recent work on the Nazarov reaction (Jalbout et al, 2007)]; therefore consideration was given for its involvement in the ring-closing mechanism of S1 to yield cyclic product S5 ϩ . This occurs through TS2, which has a forward barrier (⌬H F7 ) of Ϫ7.4 kcal/mol (MP2) and Ϫ6.9 kcal/mol (CCSD (T)//MP2) and an energy of reaction of around Ϫ25 kcal/mol at both the MP2 and CCSD (T)//MP2 levels of theory.…”
Section: H 3 O ϩ Addition Of Dimer To Intermediatementioning
confidence: 99%
“…For example, Jalbout and co-workers, based on quantum chemical calculations, have argued for the importance of hydrogen bonding to the 3hydroxy group with water in promoting cyclization [50]. Several groups have suggested that, at least in some cases, protic acids play more complicated roles, beyond merely protonating a ketone to generate a 3-hydroxy pentadienyl cation.…”
Section: Potential Dicationic Transition State Structuresmentioning
confidence: 99%
“…These were also the conditions used in our previous studies on the self-oligomerization of aldehydes. We are not the first to use computational methods to study some of the reactions in the present system; however, to our knowledge we are the first to systematically provide a broad map of the energy landscape for formaldehyde oligomerization. Previous studies typically (1) concentrated on isolated reactions of interest, (2) were for gas-phase conditions, and/or (3) were performed semiempirically.…”
Section: Introductionmentioning
confidence: 99%